Sugars determination by UPLC-MS/MS and relation with acrylamide formation in bread - Jesus, Susana (2019)
Statement of the Problem: Acrylamide is a carcinogenic contaminant produced during food processing at high temperatures. This contaminant is a Maillard Reaction product that results from a reaction between asparagine and reducing sugars. Therefore, the determination of sugar profile is an important form to understand the formation of acrylamide in foods, such as bread, potatoes or coffee. In the particular case of bread, it is important to understand the effect of fermentation on the formation of acrylamide. Until now, several techniques have been developed to determine saccharides in food, GC-MS, HPLC-DAD, HPLC-FLD, HPLC-ELSD. However, these methods have disadvantages, such as low selectivity and some methods require derivatization. Therefore, the aim of the present work was to develop a method to analyze the mono and disaccharides by UPLC-MS/MS in flour and bread dough.